Labor, work, and action: the unmaking of an LGBTIQ+ migrant network of interpreters compounding a cross-border minority tax - Monzó-Nebot, Esther (Frontiers in Communication, 2025)
International organizations have long championed principles of human rights, dignity, and equality. However, the lived experiences of LGBTIQ+ interpreters working under temporary contracts reveal structural inequalities, particularly as remote interpreting and neoliberal labor policies reshape the profession. This study conceptualizes their experiences through Hannah Arendt’s tripartite distinction between labor, work, and action to reveal how institutional structures produce and sustain a minority tax—an accumulation of burdens placed disproportionately on non-dominant identities. The research draws on semi-structured interviews conducted with twelve LGBTIQ+ interpreters employed under temporary arrangements in international organizations. Using a phenomenologically informed thematic analysis and guided by Arendt’s framework, the study explores interpreters’ narratives across three intersecting axes: gender identity, migratory status, and temporary employment. Following a hermeneutic interpretive cycle with participant feedback, the analysis reveals an increase in survival-based tasks (labor), difficulties in establishing professional continuity and recognition (work), and curtailed opportunities for political engagement (action). Arendt’s categories illuminate how the erosion of political space within international organizations depoliticizes LGBTIQ+ interpreters and impedes the formation of solidarity networks. Reforms are suggested to simultaneously address survival conditions, professional stability, and participatory agency to dismantle the mechanisms that perpetuate exclusion under the guise of flexibility and technological innovation.